Upstream Reduction of Solid Waste Generation : Implications on Dioxin and Furan Emission - World Bank (Washington, DC, 2013)
Environmental Resources Management-PR, Inc presents this report entitled 'upstream reduction of solid waste generation and its implications on dioxin and furan emissions' as part of the project phase two study upstream reduction of solid waste generation and its implications on dioxin and furan emissions, approved by the World Bank on April 19, 2011. Burning of garbage is prevalent in Latin America at poorly managed disposal sites and when it is used as a means of disposal at the household level in rural areas and other areas not adequately covered by collection. Waste burning is one of the major sources of dioxins and furans in these Countries. Current strategies to reduce these emissions include the long term process of converting dumpsites to landfills and expanding collection to areas not covered by the collection service. In addition to these programs, reduction in waste generation volume potentially present a cost-effective means to reduce overall dioxin and furan emissions and there is some evidence that reducing certain types of wastes (plastics and chlorinated polymers) will reduce the levels of dioxin and furans emitted from a given quantity waste.